2013
DOI: 10.1371/journal.pone.0058841
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiac Myocyte PDE5 Levels in Human and Murine Pressure Overload Hypertrophy Contribute to Adverse LV Remodeling

Abstract: BackgroundThe intracellular second messenger cGMP protects the heart under pathological conditions. We examined expression of phosphodiesterase 5 (PDE5), an enzyme that hydrolyzes cGMP, in human and mouse hearts subjected to sustained left ventricular (LV) pressure overload. We also determined the role of cardiac myocyte-specific PDE5 expression in adverse LV remodeling in mice after transverse aortic constriction (TAC).Methodology/Principal FindingsIn patients with severe aortic stenosis (AS) undergoing valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…(Left panel) Cardiomyocytes exposed to DOX have a tendency to change from oxidative to glycolytic mechanism and to show a functional impairment [5,63], potentially also associated with a switch to fetal gene expression program [87] {Hrelia, 2002 #97}. Likewise, while cardiomyocytes have acquired apoptosis resistance during differentiation [46], DOX exposure may change the balance of pro-and anti-apoptotic proteins in favor of the latter [25,88] or sensitize cardiomyocytes to cell death ligands [49].…”
Section: Acknowledgementmentioning
confidence: 99%
“…(Left panel) Cardiomyocytes exposed to DOX have a tendency to change from oxidative to glycolytic mechanism and to show a functional impairment [5,63], potentially also associated with a switch to fetal gene expression program [87] {Hrelia, 2002 #97}. Likewise, while cardiomyocytes have acquired apoptosis resistance during differentiation [46], DOX exposure may change the balance of pro-and anti-apoptotic proteins in favor of the latter [25,88] or sensitize cardiomyocytes to cell death ligands [49].…”
Section: Acknowledgementmentioning
confidence: 99%
“…Induction of PDE5 has been observed in rat models of mesenteric occlusion where functional studies suggested that it attenuates increased NO signaling (Zhang et al, 2009). PDE5 is also induced in heart and lung in response to chronic pressure overload (Oishi et al, 2007; Vandenwijngaert et al, 2013), and in resistance pulmonary arteries to hyperoxia (Farrow et al, 2008), and underscores the complex changes in gene expression that determine signaling through the NO/cGMP signaling pathway. To the best of our knowledge PDE5 inhibitor drugs have not been tested for salutary effects on coronary blood flow in this model of chronic coronary occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed as described previously (52). Images were obtained using an Axiovert 200M imaging microscope (Zeiss, Oberkochen, Germany).…”
Section: Histological and Immunoblot Analysismentioning
confidence: 99%